The genome sequence of the European flat oyster, Ostrea edulis (Linnaeus, 1758) [version 1; peer review: 2 approved] - Patrick Adkins; Rob Mrowicki (Wellcome Open Research, 2023)
We present a genome assembly from an individual Ostrea edulis (the European flat oyster; Mollusca; Bivalvia; Ostreida; Ostreidae). The genome sequence is 894.8 megabases in span. Most of the assembly is scaffolded into 10 chromosomal pseudomolecules. The mitochondrial genome has also been assembled and is 16.35 kilobases in length.